Crisis, end, or eclipse of reason? Max Horkheimer's Critical Theory contributions to an epistemology of eugenics - Roitberg, Guilherme Prado (Universidade Federal de São Carlos, 2022)
This article investigates the epistemological foundations of Francis Galton's eugenics based on Max Horkheimer's Critical Theory. Grounded on a bibliographical research, we analyze the texts in which the English polymath structured the rationality of his science-religion, contrasting them with the theoretical-critical diagnosis of the crisis of reason. We conclude that Horkheimer’s argument denouncing the enlightened roots of eugenics, despite not having been explored in historiography, remains fundamental to the understanding of the eugenic scientific rationality, which we denominated eugenic reason.

O presente artigo investiga os fundamentos epistemológicos da eugenia de Francis Galton a partir da teoria crítica de Max Horkheimer. Baseados em uma pesquisa bibliográfica, analisamos os textos nos quais o polímata inglês estruturou a racionalidade de sua ciência-religião, contrapondo-os com o diagnóstico teórico-crítico de crise da razão. Concluímos que o argumento horkheimeriano que denunciou as raízes esclarecidas da eugenia, a despeito de não ter sido explorado na historiografia, continua fundamental para a compreensão da racionalidade científica eugenista, a qual denominamos razão eugênica.
Crise, fim ou eclipse da razão? Contribuições da Teoria Crítica de Max Horkheimer para uma epistemologia da eugenia
Keywords: Eugenia; Razão eugênica; Esclarecimento; Teoria Crítica; Eugenics; Eugenic reason; Enlightenment; Critical Theory; Max Horkheimer; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS